Evaluating the hair regenerative potential of plant-based hair serum formulation: a comparative study - Upadhyay, Ratna; Gadani, Mihir C.; Badak, Sneha (International Journal of Scientific Reports, 2024)
Background: Hair loss, a multifactorial condition influenced by factors such as aging, hormonal imbalances, and genetics, has traditionally been treated with synthetic products like minoxidil and finasteride. However, these treatments often come with significant side effects, highlighting the need for safer and more effective alternatives. This study investigates the efficacy and safety of OZiva+ advanced hair growth serum, a formulation containing 3% Redensyl® and 1% Lindera root extract, as a potential treatment for hair loss. Methods: The serum's hair growth-promoting effects were evaluated using the ex vivo Philpott test, involving hair plucks from androgenetic alopecia patients, and its safety was assessed through a clinical patch test on human volunteers. Results: The results demonstrated a significant increase in hair follicle length with the OZiva+ advanced hair growth serum, comparable to 1% minoxidil. Additionally, the serum showed no irritation during the patch study, indicating its safety for use. Conclusions: The findings suggest that OZiva+ advanced hair growth serum is a promising alternative to traditional hair loss treatments, offering comparable efficacy with fewer side effects. This natural formulation, supported by the synergistic action of Redensyl® and Lindera root extract, holds potential for further development as a safer, more effective solution for hair regrowth and overall hair health.